Imperfect promise [large type] - Lane, Susanna (WHEELER PUBLISHING LARGE PRINT Softcover Western, 2022)
""Former gunfighter Cortland Enders is about to go to prison when the woman he works for invents a scheme to save him. Sienna Harris, widowed owner of the Circle H, makes a deal with the judge-Cort will serve his three-year sentence running the ranch, bound to it as her new husband. The marriage is in name only, enabling Sienna to leave the ranch to Cort after she dies of the cancer thats consuming her. Getting Cort to accept the deal proves more difficult. Some years back, Siennas first husband, Wade, gave the young gunslinger a place at the Circle H to soothe his tormented soul. Cort owes Wade Harris a debt and agrees only after Sienna plays on his loyalty to them both. Lark Garrin is on the run from a vicious outlaw, Will Cardin. Needing a place to hide, she ends up in Ogallala, at a "ribbon dance" for women seeking husbands. Cort is dispatched to this dance at Siennas request. He isnt looking for a wife but needs to find his wife a companion. Tempers flare when Lark discovers Cort is already married, until Sienna explains her duties. Accepting Corts protection is Larks salvation, until Cardin gets close and she flees again. Overcoming impossible odds, Cort uses his skills as a tracker and gunfighter to find her and set her free. Set on the frontier during turbulent times, this story carries its gritty and prideful characters through tragedy and mistakes, as they fulfill an imperfect promise"-"--